Presentation of Concept and Struggle of Non-Alignment Movement to Promote Multi-Nationalism in India: The Relevance and Impact of the Non-Aligned Movement in Contemporary Global Politics (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Non-Aligned Movement (NAM) developed in the context of the flood of decolonization that pursued World War II. It was established amid the stature of the Soviet-U.S. Confrontation in 1961 in Belgrade. Its political bearing has reduced in the post-cold war condition with the breaking down of USSR however NAM is as yet relevant in the present global condition. The US (United States) and European nations scrutinized NAM and repudiated it as a gathering of pioneer nations. The NAM developed as a universal stage as a third option of two power alliances. The NAM was the global phenomenon of creating and underdeveloped nations. Non-alignment became out of the virus war severe relationship among US and USSR. Some creating and third world recently independent nations would not post Second World War world politics through the eyes of their past colonial rulers. The policy will keep going as long as the sovereign state system exists. Its legitimacy can't be addressed similarly as the United Nations Organization and their sanctions are not invalidated by the wrongdoings of omissions and commissions of the association and its part states. Like UN, the destinations of NAM are to a great extent of a long haul and universalistic in nature.